Food Sources and Preferences of College Students - Deric, Deric Hardy; Godfrey, Ejimakor; Quaicoe, Obed (European Scientific Journal, ESJ, 2017)
Young adults, especially college students, in the United States (U.S.) have to make independent decisions on where to buy food and the attributes of the food to buy. For some, the decision is one of their first undertakings since leaving home and could be foundational relative to their food choices, with its attendant health implications, later in life. We used a data from a survey to ascertain the frequency with which some U.S. college students shop at different types of food vendors such as grocery stores, supermarkets, fast food restaurants and full-service restaurants. We also asked about the food attributes that were important to students. Our results indicate that supermarkets were the primary sources of food at home for the students while fast food restaurants were the dominant sources of food away from home. Taste, followed by price, were the most important food attributes for students. Most students indicated a willingness to pay more for local food and food produced on small farms. Food vendors that could provide food that tastes good at lower prices are likely to have a competitive edge in attracting college students as patrons. The interest of students in local foods suggests that the current local foods movement may not be a fad, but could be sustained for a longer period.